2015
DOI: 10.1002/etc.2866
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia stress on the carbon metabolism of Ceratophyllum demersum

Abstract: In the present study, carefully controlled pH ranges (7 and 9) were used to distinguish between the effects of un-ionized NH3 and the NH4 (+) ion. The objective was to find the effect of different total ammonia nitrogen concentrations and pH values on the carbon metabolism of Ceratophyllum demersum. The authors investigated the effects of ammonia on the nonstructural carbohydrate content in shoots of C. demersum. Ammonia treatment decreased the contents of nonstructural carbohydrate, soluble sugar, sucrose, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…In addition to excessive loading of phosphorus (P) (Scheffer, 1998; Carpenter, 2003), high nitrogen (N) loading has also been suggested to contribute importantly to the recession of macrophytes (Moss, 2001; Jeppesen et al, 2007; Moss et al, 2013). High N may cause physiological damage to the submersed macrophytes by generating oxidative stress (Wang et al, 2010; Zhang et al, 2011), disturbing the metabolism of carbon and nitrogen (Cao et al, 2009b; Gao et al, 2015; Yuan et al, 2015) and inhibiting photosynthesis (Wang et al, 2008; Su et al, 2012). High N may also affect the plants indirectly by promoting the growth of phytoplankton (Sayer et al, 2010a,b) or periphyton (Olsen et al, 2015; Zhao et al, 2016) and hence their shading effects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to excessive loading of phosphorus (P) (Scheffer, 1998; Carpenter, 2003), high nitrogen (N) loading has also been suggested to contribute importantly to the recession of macrophytes (Moss, 2001; Jeppesen et al, 2007; Moss et al, 2013). High N may cause physiological damage to the submersed macrophytes by generating oxidative stress (Wang et al, 2010; Zhang et al, 2011), disturbing the metabolism of carbon and nitrogen (Cao et al, 2009b; Gao et al, 2015; Yuan et al, 2015) and inhibiting photosynthesis (Wang et al, 2008; Su et al, 2012). High N may also affect the plants indirectly by promoting the growth of phytoplankton (Sayer et al, 2010a,b) or periphyton (Olsen et al, 2015; Zhao et al, 2016) and hence their shading effects.…”
Section: Introductionmentioning
confidence: 99%
“…Most scientists agree that phytoplankton shading promoted by increasing inputs of phosphorus is an underlying cause of the decreasing abundance, but the role of nitrogen has received increasing attention in recent years (Moss, 2001;Jeppesen et al, 2007;Moss et al, 2013). In previous studies, two main mechanisms have been identified to explain the effects of nitrogen on submersed macrophytes: 1) it promotes the growth and hence shading of phytoplankton (Sayer et al, 2010a(Sayer et al, , 2010b or periphyton (Olsen et al, 2015;Zhao et al, 2016) that uses nitrogen as its nutrient source; 2) it causes physiological stress on the submersed macrophytes and limits the metabolism of carbohydrates (Cao et al, 2009a;Yuan et al, 2015;Gao et al, 2015), inducing oxidative stress (Wang et al, 2010;Zhang et al, 2011) and inhibiting photosynthesis (Wang et al, 2008;Su et al, 2012). Experimental studies have revealed that ammonium (NH 4 )-related physiological stress may be aggravated by low light conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Of course, many factors affect glutamine synthetase enzyme activity, such as organism situation, carbohydrates, amino acids, and light exposure . It has been shown that increased ammonium N reduced the chlorophyll content of C. demersum , resulting in reduced photosynthesis activity and reduced carbohydrate production , thus indirectly influencing glutamine synthetase enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
“…The main reason may be that when a plant passively absorbs a large amount of N, ammonium N accumulation in the tissue leads to changes in the concentration of free amino acid in N metabolism. This results in substantial ammonia accumulation, physiological toxicity, and a response to this ammonia stress through a high consumption of nonstructural carbohydrates .…”
Section: Resultsmentioning
confidence: 99%